Evaluasi Workshop Perancangan Video Pembelajaran Interaktif sebagai Penunjang Kompetensi Tenaga Pendidik - Luthfiana Tarida (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2021)
The competition of educators in designing learning media is needed especially in facing the challenges of changing the educational paradigm of the Covid-19 pandemic era. This change leads to online learning to reduce the number of Covid-19 spread. Video is one of the interactive media that can be used during online learning. However, not all educators are equipped with competence in designing interactive learning videos. Workshops need to be done to support the competence of educators. Workshop evaluation also needs to be done in order to analyze the shortcomings and advantages during the implementation, so that it can be used as a basis for improvement for the next workshop. Therefore, this study aims to analyze the evaluation of the workshop. Evaluation is an evaluation of the process during the implementation of activities. This research is quantitative research with descriptive statistical data analysis techniques. The data collection instrument used is a questionnaire with a likert scale. The data is analyzed by calculating the average score of each statement item and then concluded descriptively. The results of the study inform that the workshop activities are carried out in 3 stages, namely the selection of materials that support interactive activities, video capture in accordance with the material, and video editing and materials using kinemaster applications. The conclusion of the evaluation of the workshop is that the activities have been carried out well, but there are some shortcomings such as the allocation of too little time. These shortcomings can be used as improvement materials for further workshop activities so that teacher competence can be maximized. For example,